16QAM-LFM waveform design for integrated radar and communication - Hao ZENG; Lixia JI; Feng LI; Chuang LI (Tongxin xuebao)
A kind of high-order integrated radar communication waveform pulse was proposed,which combined 16QAM and LFM together.The new waveform took LFM signal as the carrier of the 16QAM,so that high communication capacity was achieved and the radar performance was not impacted.The analysis and computer simulation for the 16QAM-LFM waveform show that the new waveform has the same bit error rate as the classic 16QAM signal and larger spectrum efficiency compared with the integrated waveforms such as BPSK-LFM and MSK-LFM.Furthermore,the computational complexity of 16QAM-LFM is less than the existing OFDM-LFM waveform.On the other hand,16QAM-LFM has higher distance resolution and speed resolution than the traditional LFM pulse signal since its ambiguity function looks like a thumb tack.And the detection probability of radar is similar as traditional LFM pulse signal for the slowly moving object.